Cost Estimation Planning Model For Implementation Of Irrigation Network Improvement Projects In East Java Province, Indonesia - Soepriyono (CV. Ulil Albab Corp, 2022)
This study generally examines, and in-depth analyses the estimated model of the planned budget plan for the Irrigation Network Improvement Project at the Public Works and Housing Department in the East Java Province, Indonesia. The research data is secondary data in the form of Recapitulation of Budget Plans (RAB) for Irrigation Works in six Cities / Regencies, such as Surabaya, Lamongan, Tuban, Pasuruan, Sidoarjo and Mojokerto, until 2013 to 2018. To equalize the homogeneity of the data, thus RAB data for each City / Regency is converted based on the HSPK of Surabaya and the project budget value is projected in 2019 based on the prevailing inflation in East Java Province. Data analysis use the Cost Significant Model method then the project budget planning. The results of the study concluded that the regression model for estimating effective, efficient and accurate project cost budget plans to be applied to the Irrigation Network Improvement Project in the Public Works and Housing Department in East Java Province is a regression equation Y = 112,545+ 11,595 X4+ 8,493 X5 + 9,247 X6. Which X4, X5 dan X6 represent landfill work, masonry work and cement mixing work per meter length of channel. Comparison of the accuracy of the estimated project cost budget plan model with the actual HPS cost estimation model obtained an upper limit of 4.20% and a minimum lower limit = - 11.500% with an average comparison of - 2.45% which is stated as excellent accuracy.